Rationale and design of the COlchicine for Prevention of the Post-pericardiotomy Syndrome and Post-operative Atrial Fibrillation (COPPS-2 trial): A randomized, placebo-controlled, multicenter study on the use of colchicine for the primary prevention of the postpericardiotomy syndrome, postoperative effusions, and postoperative atrial fibrillation - Imazio, Massimo; Belli, Riccardo; Brucato, Antonio; Ferrazzi, Paolo; Patrini, Davide; Martinelli, Luigi; Polizzi, Vincenzo; Cemin, Roberto; Leggieri, Anna; Caforio, Alida L.P.; Finkelstein, Yaron; Hoit, Brian; et al. (The American heart journal, 2013)
The efficacy and safety of colchicine for the primary prevention of the postpericardiotomy syndrome (PPS), postoperative effusions, and postoperative atrial fibrillation (POAF) remain uncertain. Although preliminary data from a single trial of colchicine given for 1 month postoperatively (COPPS trial) were promising, the results have not been confirmed in a large, multicenter trial. Moreover, in the COPPS trial, colchicine was given 3 days postoperatively. The COPPS-2 study is a multicenter, double-blind, placebo-controlled randomized trial. Forty-eight to 72 hours before planned cardiac surgery, 360 patients, 180 in each treatment arm, will be randomized to receive placebo or colchicine without a loading dose (0.5 mg twice a day for 1 month in patients weighing ≥70 kg and 0.5 mg once for patients weighing <70 kg or intolerant to the highest dose). The primary efficacy end point is the incidence of PPS, postoperative effusions, and POAF at 3 months after surgery. Secondary end points are the incidence of cardiac tamponade or need for pericardiocentesis or thoracentesis, PPS recurrence, disease-related admissions, stroke, and overall mortality. The COPPS-2 trial will evaluate the use of colchicine for the primary prevention of PPS, postoperative effusions, and POAF, potentially providing stronger evidence to support the use of preoperative colchicine without a loading dose to prevent several postoperative complications. ClinicalTrials.gov Identifier: NCT01552187.